The Impact of Artificial Intelligence on Personalized Learning: A Systematic Literature Review - Salis Irvan Fuadi (Penelitian dan Pengembangan Ilmu, 2024)
The use of artificial intelligence (AI) in higher education is increasing, but understanding of its impact on personalized learning remains limited. This research aims to systematically examine how AI influences personalized learning and to explore the challenges and opportunities that exist. Through a systematic literature review method, the results show that AI increases student effectiveness, engagement, and motivation, but also faces challenges related to data privacy and acceptance of the technology by educators. These findings have important implications for stakeholders in designing educational strategies that are more adaptive and responsive to individual needs.